Calcitonin Gene‐Related Peptide Receptor Antagonists (Gepants) for the Acute Treatment of Nausea in Episodic Migraine: A Systematic Review and Meta‐Analysis - Chan, Tommy Lik Hang; Cowan, Robert P.; Woldeamanuel, Yohannes W. (Headache, 2020)
Objective To synthesize the evidence on the efficacy of calcitonin gene‐related peptide receptor antagonists (gepants) from all clinical trials addressing nausea treatment for episodic migraine. Introduction Nausea is one of the most bothersome symptoms in patients with migraine. The most bothersome symptom is part of the outcomes explored in clinical trials. Methods Published clinical trials for this project were identified via searches of 4 bibliographic databases: PubMed (includes MEDLINE), Embase, Web of Science, and the Cochrane Library. Individual search strategies included terms related to calcitonin gene‐related peptide, nausea, and vomiting. Random‐effects meta‐analysis was conducted to estimate the overall efficacy of gepants for nausea treatment. Heterogeneity, publication bias, small‐study bias, and potential confounders were explored using Galbraith plot, sensitivity analysis, meta‐regression, and Egger’s regression tests. Cumulative meta‐analysis was done to detect temporal trend from accumulating trials. Results The meta‐analysis involved 23,008 participants in 65 clinical trials from 14 published articles; 10,770 subjects participated in gepant treatment arms while 12,238 subjects participated in placebo or non‐gepant arms (85% females, mean age 41 years in both arms). Nearly all studies used a 2‐hour incidence of nausea as an outcome measure. An overall combined effect size with an odds ratio of 1.29 (95% CI 1.18, 1.40, P = .001; I2 = 42.8%) showed the efficacy of gepants for the treatment of nausea in episodic migraine. Galbraith plot demonstrated that 98.4% of studies were within 2 standard deviations from the regression line, indicating lack of significant heterogeneity and outliers. Meta‐analysis results were robust to sensitivity analysis, small‐study bias, and publication bias (Kendall’s Tau −0.09, P = .29; Egger's regression P = .67). Meta‐regression showed that both age and sex ratio were not confounding the meta‐analysis (omnibus P = .69). Cumulative meta‐analysis indicated that the effect size remained stable for studies conducted after 2011, with accumulating evidence continuing to favor efficacy of gepants for the treatment of nausea in episodic migraine. Conclusion There is sufficient evidence to support the efficacy of gepants for the treatment of nausea in episodic migraine. Future research may focus on examining this efficacy in under‐represented patient populations (males, older age groups) and in chronic migraine.